Prince - "Machiavelli, Niccolo" (New York, 2007)
The first modern treatise of political philosophy, The Prince is one of the world$1 (Bs most influential and widely read books. Machiavelli reveals nothing less than the secrets of power: how to gain it, how to wield it, and how to keep it. Ruthless, cunning, and amoral, The Prince is a controversial analysis of manipulation and an essential guide for anyone interested in conquest, self-defense, or observation of dominance and control. The Introduction by noted Italian Renaissance scholar Albert Russell Ascoli provides a perfect opening to Peter Constantine$1 (Bs illuminating new translation of this seminal work.s
Keywords: Political science - Early works to 1800